S77 Effects of bisoprolol and celiprolol on cardiopulmonary performance in COPD. (12th November 2019) - Anderson, WJ; Short, PM; Jabbal, S; Kuo, RW; Ross, RA; Morrison, AE; Lipworth, BJ
Abstract : Background: Beta-blockers (BB) are underused in COPD despite evidence for reducing mortality from cardiovascular comorbidities. Beta-1 selective antagonists such as bisoprolol (BIS) may cause bronchoconstriction due to dose related beta-2 blockade. Celiprolol (CEL) is a beta-1 selective antagonist which also exhibits partial beta-2 agonist activity. Patients with COPD can get dynamic hyperinflation (DH) upon exercise which in turn can impair cardiopulmonary performance. We have therefore compared for the first time the chronic dosing effects of BIS and CEL on cardiopulmonary exercise testing (CPET) in patients with COPD. Patients and methods: Patients with moderate to severe (GOLD 2/3) COPD were enrolled to receive in randomised crossover fashion either BIS 2.5 mg od (2 weeks) followed by 5 mg od (2 weeks) or CEL 200 mg od (2 weeks) then 400 mg od (2 weeks). CPET to symptom limit using cycle ergometer at constant work rate was performed at baseline pre-BB and post-BB at 4 weeks. Results: 11 patients with COPD were enrolled: 7M4F; Age 69yr (95%CI:65–73yr); Post-salbutamol FEV1 56% (95%CI:49–63%); FVC 100% (95%CI:86–114%); FEV1 /FVC 46% (95%CI:36–53%); RV/TLC 50% (95%CI:44–56%). 10 patients were taking long-acting beta-agonists, 10 patients long-acting muscarinic antagonists and 6 patients inhaled corticosteroids. Inspiratory capacity (IC) showed a significant fall when comparing rest vs isotime peak exercise (4 min) in keeping with DH, with no differences post exercise for baseline vs either BB (figure 1A). Borg scales for dyspnoea (figure 1B) and perceived exertion on exercise were no different from baseline vs BB. Peak exercise heart rate was significantly lower comparing baseline vs BB, with resting heart rate only significantly lower with BIS and not CEL (figure 1C). Resting and peak exercise cardiac output were not significantly different comparing baseline vs BB (figure 1D). A significant difference was seen for mean arterial blood pressure between rest and peak exercise at baseline but not after BB. Lung function as FEV1, FVC, Relaxed VC and RV/TLC ratio were not significantly altered by either BB vs baseline. Conclusions: Overall cardiopulmonary performance was relatively well preserved while taking BB. Our results support the more widespread use of cardio-selective BB in patients with COPD who have cardiovascular comorbidity.